Cross-trait genetic enrichment between GERD and psychiatric disorders in East Asian populations - Gao, Zhihao; Wang, Xianjin; Liu, Zekun; Hu, Fen; Zhou, Yidi; Ullah, Kalim; Wang, Ruiwei; Zhang, Meng; Chang, Xiao; Wang, Yongsen (Frontiers in Genetics, 2026)
Gastroesophageal reflux disease (GERD) exhibits significant epidemiological comorbidity with psychiatric disorders, yet their shared genetic architecture remains poorly characterized in East Asian populations. Leveraging ancestry-specific genome-wide association study (GWAS) summary statistics from East Asian cohorts, we employed linkage disequilibrium score regression and conditional false discovery rate (condFDR) approaches to investigate cross-trait genetic enrichment between GERD and major psychiatric disorders, including major depressive disorder (MDD), schizophrenia (SCZ), and bipolar disorder (BIP). We identified significant genetic correlations between GERD and both MDD (rg = 0.49, P = 0.03) and SCZ (rg = 0.25, P = 0.02), but not with BIP. Through condFDR analysis, two novel loci were discovered: rs3980178 near MEIS1(associated with GERD-MDD pleiotropy) and rs9844126 near ZBTB20(associated with GERD-SCZ pleiotropy). These loci are implicated in neurodevelopment, autonomic regulation, and neural circuit formation, providing mechanistic insights into the gut-brain axis. Our findings demonstrate that cross-trait genetic enrichment significantly enhances locus discovery for GERD in underpowered East Asian GWAS and reveal ancestry-specific genetic links between gastrointestinal and psychiatric phenotypes.